Immunohistochemical expression of inflammatory markers in sudden infant death; ancillary tests for identification of infection. Issue 12 (3rd October 2014) - Pryce, J W; Bamber, A R; Ashworth, M T; Klein, N J; Sebire, N J
Abstract : Aims: Sudden unexpected death in infancy (SUDI) investigation requires extensive ancillary investigations, the results of which, such as postmortem microbiology, can be difficult to interpret. Markers of an inflammatory response, including interleukin 6 (IL-6), c-reactive protein (CRP) and cellular adhesion molecules are elevated in infections, yet little attention has been paid to their assessment after death. This study investigates the role of inflammatory markers in SUDI autopsies for determining cause of death. Methods: Cases of SUDI over a 14 year period were identified from an autopsy database and 100 cases were selected for immunohistochemical staining of heart and liver for IL-6, CRP, P-selectin, VCAM-1 and ICAM-1 (CD54), with staining patterns compared between five groups, including infectious and unexplained SUDI. Results: There were significant differences between groups. Cases of histological infection demonstrated strongly positive hepatocyte CRP and ICAM-1 expression and increased myocardial staining for CRP. Half of trauma-related deaths demonstrated diffuse hepatic CRP expression but without myocardial CRP staining. Staining of unexplained SUDI cases were predominantly negative, apart from a subgroup in whom Escherichia Coli was identified, who had increased expression of hepatic IL-6. Conclusions: There were distinct patterns of organ-specific CRP and ICAM-1 expression in SUDI by cause of death. These markers of inflammation were rarely present in unexplained SUDI suggesting either a non-inflammatory cause of death or a failure to mount an effective acute phase response. Immunohistochemical staining offers potential to identify infection-related deaths and provides insight into SUDI mechanisms.